Combination of Amniotic Membrane Stem Cell Metabolite Product (AMSC-MP) and Vitamin E for Photoaging - Retha Retha; Sawitri Sawitri; Rahmadewi Rahmadewi; Afif Nurul Hidayati; Muhammad Yulianto Listiawan; Evy Ervianti; Linda Astari; Cita Rosita Sigit Prakoeswa (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2020)
Background: It is hypothesized that combination of amniotic membrane stem cell metabolite product (AMSC-MP) and vitamin E after fractional CO2 laser as laser assisted drug delivery (LADD) provides better long-term effects on clinical improvement of photoaging. This is promising as an option for photoaging therapy in the future. Purpose: The study aimed to evaluate long-term effects of improving the degree of wrinkles, polarized black spots, ultraviolet (UV) black spots, pores, and skin tones in subjects who have received a topical mixture of AMSC-MP with vitamin E and CO2 fractional laser as LADD. Methods: Thirty adult women with photoaging who had been treated with topical AMSC-MP mixed therapy with vitamin E and CO2 fractional laser three times, were then given maintenance therapy, tretinoin cream 0.025% and sunscreen SPF 30. Observation of improvement of wrinkles, polarized black spots, UV black spots, pores, and skin tones were performed computer-stimulated photographs, Janus-II Facial Skin Scope System, three times every month for three months after the last treatment. Results: The evaluation of wrinkles, polarized black spots, UV dark spots, pores and skin tones from the assessment for three months after being receiving treatment of a topical mixture of AMSC-MP with vitamin E and CO2 fractional laser as LADD on photoaging obtained p>0.05. Conclusion: There was a long-term effect of the topical mixture of AMSC-MP with vitamin C and CO2 fractional laser on photoaging, and there was no side effect observed.